Estimation of the Amount of possible organ donors in Sergipe/Brazil in 2007 - Rodrigues, Thais Kuhn; Alves Júnior, Antônio (Brazilian Journal of Transplantation, 2010)
Transplant is the best treatment option for some terminal diseases in organs and the only option to interfere in the natural evolution of some kind of insufficiencies. Still, the main source of organs for transplantation is the corpse donor and this amount is not enough to attend the demand due to failures in many parts of the donation-transplant process. Purpose: To estimate the amount of possible organ and tissue donors in Sergipe; identify the profile of these possible donors; to calculate donation rates, notification and the reclamation of organ donors in this state. Methods: Quantitative, descriptive and retrospective research in which data gathered from the necropsy reports of the Forensic Institute of Sergipe and from the patient’s charts reported in the state Transplant Center on the same period was used. Results: 1388 necropsy reports related to the deaths occurred from January 1st to December 31st 2007 were analyzed, from which 128 (9.22%) possible donors were selected, being 108 (84.4%) of the male gender. The average age was 30.95 years old and the uppermost age group was from 21 to 40 years old, represented by 54.4% persons. In the majority (86%), victims were attended at the Emergency Hospital of Sergipe, which is the reference in trauma in this state, and the cause of the death in 78 cases (60.94%), was traffic accident. In such period, there were 89 notifications to the Transplant Center, being 28 due to brain death. 50 donations were executed: 41 were strictly corneas, 8 corneas and kidneys and 1 of multiple organs. The notification index was 1:5.82; the utilization rate of notifications was 56.17%; the notification rate was 0.46 pmp and the donation rate 0.26 pmp. Conclusion: There was a low utilization in the amount of potential donors, and therefore, actions involving all society levels are necessary with the overall purpose to increase the amount of donations and transplants in Sergipe.